Nutrition Intervention for Older Patients Based on Comprehensive Geriatric Assessment: A Case Report - Dasom Park; Ah-reum Shin; Youngmi Park (Clinical nutrition research, 2025)
Malnutrition is prevalent among older patients, leading to increased morbidity, prolonged hospitalization, and diminished quality of life. The Comprehensive Geriatric Assessment (CGA) facilitates the evaluation of multifaceted health issues, enabling individualized nutritional interventions. This case report describes nutritional management guided by CGA in a 75-year-old female hospitalized for severe hypernatremia with significant malnutrition and high-risk for refeeding syndrome. Upon admission, CGA identified multiple comorbidities, cognitive impairment, and complete dependence on caregivers for daily activities. Due to persistent refusal of oral intake, enteral nutrition (EN) was cautiously initiated at 25% of the target energy requirement, with close monitoring of electrolyte levels. Despite an initial decrease in phosphorus levels suggestive of refeeding syndrome, gradual advancement of nutritional support successfully stabilized her clinical condition. Following discharge, structured caregiver education was provided to support EN at home; however, suboptimal intake persisted due to gastrointestinal intolerance, resulting in weight loss. Post-discharge follow-ups identified feeding rate-related symptoms, necessitating formula adjustments and caregiver re-education. This case emphasizes the critical role of CGA in early malnutrition detection, individualized nutritional intervention, prevention of refeeding syndrome, and the importance of continuous post-discharge monitoring and caregiver education. Although the findings are limited by the single-case design, proactive CGA-based nutritional interventions remain crucial for optimizing clinical outcomes in older patients hospitalized due to acute medical problems. Further research involving larger samples and prolonged follow-up periods is required to validate the long-term benefits of CGA-based nutritional intervention.